Identification of Malassezia furfur in Skin Scrapings of Elementary School Students in Antiga Village, Karangasem, Bali - Bintari, Ni Wayan Desi; Pradnyawati, Ni Luh Mona; Idayani , Sri (Program Studi Teknologi Laboratorium Medis, 2025)
Fungal skin infections that have a fairly high prevalence in the community are tinea versicolor or Tinea Versicolor. Tinea Versicolor generally occurs in individuals with poor hygiene and sanitation conditions. School-age children have a fairly high risk of being infected with Tinea versicolor due to their high physical activity. The purpose of this study was to determine the results of Malassezia furfur identification in skin scrapings of students at State Elementary School 6 in Antiga Village, Karangasem Regency, Bali. This type of research uses a descriptive study to identify the fungus that causes tinea versicolor in students' skin scrapings using direct observation methods. The samples in this study were skin scrapings from 30 students selected using purposive sampling techniques. Laboratory examinations for Malassezia furfur identification were carried out at the Parasitology and Mycology Laboratory of STIKES Wira Medika Bali using direct observation. The results showed that out of 30 samples examined, 20 samples (67%) showed positive results for the identification of Malassezia furfur in their skin-scraping specimens and 10 samples (33%) showed negative results. Reviewed based on the frequency distribution of Malassezia furfur identification results based on gender, it is known that out of 20 positive results, 2 were female (10%) and 18 were male (90%). Based on the results of this study, it was concluded that in the sample population studied, there was a relatively high prevalence of Tinea versicolor, which was around two-thirds of the total samples examined